Congenital Temporomandibular Joint Ankylosis: Case Report and Literature Review - Ryan Chin Taw Cheong; Karim Kassam; Simon Eccles; Robert Hensher (Case Reports in Otolaryngology)
Congenital temporomandibular joint (TMJ) ankylosis is an uncommon condition that presents itself at or soon after birth in the absence of acquired factors that could have contributed to the ankylosis such as infection and trauma. The experience of managing one such case is reported in light of a review of the literature on this condition. Key management principles include adequate removal of the ankylotic mass, costochondral grafting, and post-op physiotherapy. Most patients reported in the literature with the condition experienced relapse. This echoes our own experience where there was recurrence of the ankylosis. However, after removal of the ankylotic mass, the patient maintains a satisfactory maximal incisal opening (MIO) till the present day. The additional challenges faced in the congenital form in addition to the already complex management of acquired paediatric temporomandibular joint ankylosis are (1) much earlier insult to the TMJ, (2) reduced opportunity for neuromuscular development of the muscles of mastication, and (3) reduced compliance with postoperative physiotherapy programmes due to the younger age of these patients.